Regional politics: the importance of regional planning bodies in ensuring effective communication and collaboration - Nelson, Andria M. (Kansas State University, 2011)
Regions are an intricate network of communities, geographies and economies that together impact the long-term growth and stability of one other. Cooperation between municipalities within the same region is vital in order to achieve sustained growth, both economically and in the built environment. The research question states: What is the value of regional planning bodies in ensuring effective communication and collaboration among region-wide governmental and non-governmental agencies? This research report includes a detailed history of the role and significance of regional planning bodies in the United States, as well as a case study involving the regional planning body in Houston, Texas and the Gulf Coast Region. The Houston-Galveston Area Council is the lead participant in a 25-member coordinating committee working together to complete a regional sustainability plan under the federally funded Sustainable Communities Regional Planning Grant Program. The interviews included in this report give conclusions and recommendations to the success of the region working together in terms of communication and collaboration. The challenge of establishing effective collaboration among a variety of agencies in the Gulf Coast Region is proving to be difficult and slow moving, however, there are signs of improvement as the three-year grant program moves forward. The conclusions from the literature review and case study show that regions with an unbiased planning body benefit both from the communication and social capital gained by working together on a shared goal.
Keywords: Regional planning; Houston, Texas; Communication; Collaboration; Regional planning grant; Sustainability (0640); Urban Planning (0999)